Penguatan Kapasitas Aparatur Daerah dalam Rekonsiliasi Data Keuangan antara Rekening Koran Bank dan SIPD di Kabupaten Sumbawa - Muhammad Ikhwan; Subhan Purwadinata (Institut Nalanda, 2026)
This community service activity was carried out at the Sumbawa Regency Regional Finance and Asset Agency with the aim of supporting the capacity building of local government officials in the process of reconciling financial data between bank statements and the Local Government Information System (SIPD). The method used in this activity was participatory mentoring through direct involvement in the administration and management of local government finances. Activities carried out included matching bank statement transaction data with data in the SIPD for the March and April 2025 periods, assisting with the posting and unposting of local government journals, assisting with financial document administration, assisting with the scanning of reconciliation minutes, and supporting the verification and return of audit documents. The results of the activities indicate that the mentoring provided helped facilitate the local financial administration process, particularly in data reconciliation and the management of administrative documents that require a high degree of precision. The use of SIPD helped make the recording and management of financial transactions more systematic and integrated, thereby supporting the work efficiency of local government officials. In addition to providing benefits for the agency, this community service activity also provided practical experience for students in understanding digital-based local financial management and public financial administration processes firsthand. Thus, the community service activity contributed to supporting administrative efficiency, strengthening the capacity of local government officials, and optimizing digital-based local financial management.